La garanzia dell’ osservanza delle norme sulla competenza giurisdizionale nella proposta di revisione del Regolamento «Bruxelles I» - Franzina, Pietro (CUADERNOS DE DERECHO TRANSNACIONAL, 2011)
The proposed regulation aimed at amending (EC) regulation no. 44/2001 (the «Brussels I» regulation), presented by the Commission on 14 December 2010, purports to modify inter alia the rules governing the examination of issues of jurisdiction within proceedings in civil and commercial matters. According to the proposal, the seised court should always declare of its own motion that it has no jurisdiction, if that is the case according to the regulation (existing rules only require an ex officio declaration only where the defendant, domiciled in a Member State, does not enter an appearance, and when the courts of another Member State have exclusive jurisdiction to hear the case). The Commission’s proposal further provides that in matters relating to insurance or to consumer and employment contracts, the document instituting the proceedings should contain information for the defendant as to his right to contest the jurisdiction of the court and the consequences of entering an appearance (at present, no information in this respect is required by the regulation). On the background of these amendments lies a decision taken by the drafters of the proposal: the decision of abolishing the obstacles that, today, according to Article 35 of the regulation, prevent a judgment from being recognised and enforced abroad for reasons relating to the lack of jurisdiction of the court that rendered it. The paper proposes a critical assessment of the proposed modifications. It also deals with an issue, connected with the foregoing, which the Commission’s proposal appear to neglect: the issue regarding the cross-border effects of judgments and the question regarding how proceedings instituted before one court might be «transferred» to the court of a different Member State as a consequence of the former declaring his lack of jurisdiction.